Intentions to call a helpline among victims of intimate partner violence: The role of the Theory of Planned Behavior and Gender Role Conflict - Reis, E.; Moleiro, C.; Arriaga, P. (Violence and Victims, 2023)
This research first aimed to test the Theory of Planned Behavior (TPB) as a model to understand the intentions to call a helpline of victimized males and females. A sample of 99 participants (53 males; 46 females) who were suffering violence at the time of participation were considered for analysis. Our results indicate that males and females’ attitudes and subjective norms significantly predicted intentions. Second, this study aimed to measure Gender Role Conflict (GRC) in victimized men and test its association with TPB constructs. GRC occurs when rigid, sexist, or restrictive gender roles result in the restriction, devaluation, or violation of others or the self. Our results indicate that GRC was only negatively associated with perceived behavioral control. Additionally, in our sample of men who filled the GRC measure (n = 245), victimized men reported significantly higher GRC than non-victimized men. Overall, our findings indicate gender specificities in the intentions to call a helpline and suggest that GRC plays an important role in seeking help for men.